ROLE OF DEXMEDETOMIDINE AS AN ADJUVANT TO LIDOCAINE AND BUPIVACAINE COMBINATION AS LOCAL ANESTHETICS IN PATIENTS UNDERGOING EXTERNAL DACRYOCYSTORHINOSTOMY - SIVA SANKAR PR; PRASAD YMS (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The objective of the present study is to review the role of dexmedetomidine, its safety and efficacy when added to lidocaine and bupivacaine mixture to obtain local infiltration anesthesia (LA) in external dacryocystorhinostomy (DCR). Methods: A double-blind study was conducted to assess the role and efficacy of dexmedetomidine added to lidocaine and bupivacaine mixture to obtain local infiltration anaesthesia in External Dacryocystorhinostomy. In Group A of 32 patients 20 μg dexmedetomidine was added to 3.5 mL lidocaine 2% without epinephrine and bupivacaine 0.5% mixture as a local anesthetic. In Group B of 32 patients 3.5 mL of lidocaine 2% without epinephrine and bupivacaine 0.5% mixture alone was used as local anaesthetic. The onset and the duration of sensory blockade as well as intraoperative sedation were verified. Visual analog score was used to evaluate the post-operative pain during the 12 h postoperative period. Anesthesia-related intra-operative complications and patient satisfaction were observed. Results: Group B patients developed Anaesthesia in short duration; duration of the anesthetic effect was for long period than in the Group A (p-value was 0.015 and 0.0001, respectively). The Visual Analog Scale score of the analgesia during the post-operative period was much lower (0–3) in the study Group B than in the Group A patients (4 and 5). These values were recorded after 6th and 8th hours postoperatively with p-values at 0.002 and 0.031, respectively. Conclusion: Dexmedetomidine added to the local anesthetic agents acts as an adjuvant to produce an early sensory block, extended nerve block time, and post-operative analgesia without side effects and complications. Extended post-operative analgesia was associated with increased intraoperative sedation. Subjective satisfaction of the patients was achieved without side effects. Keywords: Lacrimal apparatus, Dacryocystorhinostomy, Local anesthetic, Sedation, Analgesia and Dacryocystorhinostomy.